Heart Rate Variability and Cardiopulmonary Dysfunction in Patients with Duchenne Muscular Dystrophy: A Systematic Review - da Silva, Talita Dias; Massetti, Thais; Crocetta, Tânia Brusque; de Mello Monteiro, Carlos Bandeira; Carll, Alex; Vanderlei, Luiz Carlos Marques [UNESP]; Arbaugh, Carlie; Oliveira, Fernando Rocha; de Abreu, Luiz Carlos; Ferreira Filho, Celso; Godleski, John; Ferreira, Celso (Springer Nature, 2018)
Duchenne muscular dystrophy (DMD) is a genetic recessive disorder with progressive muscle weakness. Despite the general muscle wasting, degeneration and necrosis of cardiomyocytes have been the main causes of morbidity and death in individuals with DMD. Cardiac failure is generally preceded by disturbances in heart rate variability (HRV), and non-invasive measurement of the autonomic nervous system has been an important tool to predict adverse cardiovascular events. Hence, the application of HRV to study autonomic modulation in DMD individuals, and the establishment of correlations between HRV and heart/lung diseases, age, and mortality will have the potential to improve quality of life and life expectancy of individuals with DMD. In order to evaluate the state of the art in this field, we conducted a systematic search in Medline/PubMed and BVS (virtual library in health) databases. We selected 8 studies using pre-defined criteria and meta-analysis revealed decreased parasympathetic activity and increased sympathetic predominance in individuals with DMD as major observations. Moreover, there is a strong association between diminished HRV and myocardial fibrosis with DMD. These patterns are evident in patients at early-stage DMD and become more prominent as disease severity and age increase. Thus, data minning clearly indicates that HRV assessment can be used as a predictor for sudden death in individuals with DMD. The use of the HRV, which is inexpensive, ubiquitously available in clinics and hospitals, and a non-invasive analysis tool, can save lives and decrease the morbity in DMD by alerting care givers to consider autonomic nervous system intervention.
Keywords: Autonomic modulation; Cardiomyopathy; Duchenne muscular dystrophy; Heart rate variability